Структурно-полевой подход к синтаксической фразеологии русского языка. Часть I - Pavlova, Anna (Przegląd Wschodnioeuropejski, 2023)
The paper deals with the problems of the structural-field approach to the study of linguistic phenomena. The foundations for building a field theory in the grammatical structure of language were laid by V. G. Admoni in his works on the theoretical grammar of German. Effectively, the same approach can be applied to any language phenomenon as it has a number of advantages over classifications involving the distribution of objects in systems of level hierarchy. The paper demonstrates the advantages and possibilities of the structural-field approach. It aims at studying the field of syntactic phraseological phenomena (phraseme constructions), identifying its core, centre, periphery, and adjacent fields. Phraseme constructions belong to the linguistic system and occupy an important place in construction grammar. They are constantly reproduced in spoken language and filled in with concrete vocabulary. They are stable syntactic models of idiomatic character that are retrieved from memory as whole entities rather than by separate units (the meaning of a filled model cannot be deduced without prior knowledge of its structure and its semantics per se). The properties, namely polyelementality, reproducibility, stable syntactic structure, idiomaticity, fillability in speech, are indispensable characteristics of the phenomenon described herein: deprived of at least one of them, a construction ceases to be a phraseme. However, phraseme constructions have a larger, typical set of characteristics. In this paper, they are viewed from the perspective of an increase and decrease of these characteristics, making the study of phraseological constructions as a field whose structure is determined by multiple axes possible. The structural-field approach waives the need to make clear distinctions between linguistic phenomena with similar functionality at different levels. The use of the field approach and its methodological advantages are explained through the example of the field of syntactic phraseology.